2021
DOI: 10.1242/jeb.242637
|View full text |Cite
|
Sign up to set email alerts
|

Communication with self, friends and foes in active-sensing animals

Abstract: Animals that rely on electrolocation and echolocation for navigation and prey detection benefit from sensory systems that can operate in the dark, allowing them to exploit sensory niches with few competitors. Active sensing has been characterized as a highly specialized form of communication, whereby an echolocating or electrolocating animal serves as both the sender and receiver of sensory information. This characterization inspires a framework to explore the functions of sensory channels that communicate inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 184 publications
0
23
0
Order By: Relevance
“…Echolocating bats use self-generated sounds for orientation and foraging, acting as a biological model for active sensing. 7 , 8 Echolocating bats require high hearing sensitivity for analyzing echo returns merely milliseconds after call production. 9 , 10 , 11 , 12 The auditory processing of echo returns in echolocating bats is thus vulnerable to self-generated masking from call production.…”
Section: Introductionmentioning
confidence: 99%
“…Echolocating bats use self-generated sounds for orientation and foraging, acting as a biological model for active sensing. 7 , 8 Echolocating bats require high hearing sensitivity for analyzing echo returns merely milliseconds after call production. 9 , 10 , 11 , 12 The auditory processing of echo returns in echolocating bats is thus vulnerable to self-generated masking from call production.…”
Section: Introductionmentioning
confidence: 99%
“…Most insectivorous bats live in highly clustered groups and rely relatively little on vision due to their nocturnal lifestyles (Chaverri et al, 2018). Bats rely on acoustic signals for orientation and communication (Bradbury & Vehrencamp, 1976; Brown, 1976b; Gould, 1971; Jones et al, 2021). Compared to vision, bat acoustic signals are less influenced by obstacles and have no light limitations (Forrest, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Bats rely on acoustic signals for orientation and communication (Bradbury & Vehrencamp, 1976;Brown, 1976b;Gould, 1971;Jones et al, 2021). Compared to vision, bat acoustic signals are less influenced by obstacles and have no light limitations (Forrest, 1994).…”
mentioning
confidence: 99%
“…Recently, the results of habituation-dishabituation playback experiments have shown that Rhinolophus clivosus discriminate between sex and individuals via their echolocation pulses alone, and researchers have found that the echolocation calls of R. clivosus have significant structural variations that may be helpful for reliable individual identification in large groups comprised of many individuals [ 27 ]. These studies reported that echolocation calls have a communicative function and play an important role in intraspecific social interactions [ 13 , 28 , 29 ]. However, while research on the acoustic communication of bats is rapidly growing, it still lags behind other mammalian taxa in general compared to the high species diversity of bats (over 1400 species worldwide [ 30 ]) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%